2022
DOI: 10.18280/ria.360106
|View full text |Cite
|
Sign up to set email alerts
|

Security of Federated Learning: Attacks, Defensive Mechanisms, and Challenges

Abstract: Recently, a new Artificial Intelligence (AI) paradigm, known as Federated Learning (FL), has been introduced. It is a decentralized approach to apply Machine Learning (ML) on-device without risking the disclosure and tracing of sensitive and private information. Instead of training the global model on a centralized server (by aggregating the clients’ private data), FL trains a global shared model by only aggregating clients’ locally-computed updates (the clients’ private data remains distributed across the cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…Non-split VFL Non-split VFL with coordinator [10], [21], [22] Non-split VFL without coordinator [11], [23], [24] Split VFL [25]- [27] Customized VFL [28]- [30] Figure 2: Taxonomy of VFL algorithms.…”
Section: Vfl Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-split VFL Non-split VFL with coordinator [10], [21], [22] Non-split VFL without coordinator [11], [23], [24] Split VFL [25]- [27] Customized VFL [28]- [30] Figure 2: Taxonomy of VFL algorithms.…”
Section: Vfl Algorithmsmentioning
confidence: 99%
“…In the non-split VFL, each participant has a full model, and it computes the gradient according to (i) the local data it owns and (ii) the intermediate information (i.e., softmax) provisioned by other participants. According to the different organizing means of participants, the non-split VFL can be further divided into non-split VFL with coordinator [10], [21], [22] and non-split VFL without coordinator [11], [23], [24].…”
Section: A Non-split Vflmentioning
confidence: 99%
“…The authors suggested a technology stack and valuable directions to mitigate those vulnerabilities. Benmalek et al [307] provided a holistic view of the security concerns in the FL paradigm. The authors have discussed various attacks and vulnerabilities in FL and recently developed promising defense mechanisms against them.…”
Section: B Potential Opportunities For Future Research In Privacy Domainmentioning
confidence: 99%
“…However, methods such as advanced Byzantine actor detection and ML using model distillation were proposed. (Benmalek, M., Benrekia, M. A., & Challal, Y. ,2022)( Hayes, J., & Ohrimenko, O. ,2018),(Li, D., & Wang, J. ,2019…”
Section: Defensesmentioning
confidence: 99%